From grit to flourishing: physical literacy’s mediating role in enhancing well-being among college students with obesity - Liu, Xingyu; Li, Zidong; Cheng, Wanru; Zhang, Jian; Ma, Xiaoyu; Tang, Di; Liu, Jinde; Gao, Tianyu; Liu, Ting; Chen, Tao; Ma, Ruisi (PeerJ, 2025)
Objective To investigate whether physical literacy mediates the relationship between grit and well-being among college students with obesity. Methods A total of 385 students with obesity were recruited. Participants completed validated questionnaires measuring grit, physical literacy, and well-being. Mediation analyses were performed to estimate indirect effects and generate bias-corrected 95% confidence intervals (CI). Results Grit was positively associated with physical literacy, and physical literacy was positively associated with well-being. Physical literacy partially mediated the relationship between grit and well-being, with the indirect effect accounting for 26.32% of the total effect (indirect effect = 0.20, 95% CI [0.09–0.31]). In a parallel mediation model analyzing the subdimensions of physical literacy, the “interaction with the environment” emerged as the strongest mediator (indirect effect = 0.15, 95% CI [0.10–0.21]), accounting for 19.74% of the total effect. The indirect effects through “motivation” and “confidence and physical competence” were also significant but accounted for smaller proportions of the total effect (6.58% and 5.26%, respectively). Conclusions These findings serve as an initial step in understanding how physical literacy, particularly the ability to interact with the environment, partially mediates the relationship between grit and well-being among college students with obesity. Future interventional research aiming to enhance physical literacy—especially environmental engagement—is needed to confirm whether it can amplify the positive impact of grit on well-being. A multifaceted approach that fosters both psychological traits and physical competencies may prove beneficial in improving the psychological and physical health of this population.
Keywords: Grit; Physical literacy; Well-being; Obesity; College students; Mediation analysis